2006
DOI: 10.1057/palgrave.mel.9100160
|View full text |Cite
|
Sign up to set email alerts
|

An Analytic Hierarchy Process (AHP) Approach to Port Selection Decisions – Empirical Evidence from Nigerian Ports

Abstract: This study presents the findings of a survey to determine the service characteristics that shippers consider important when selecting a port and the way these characteristics are prioritised according to their importance. Seven criteria for the port selection decision and four ports were identified, and the decision problem was structured into a three-level hierarchy using the Analytic Hierarchy Process. The findings suggest that shippers place high emphasis on efficiency, frequency of ship visits and adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(86 citation statements)
references
References 25 publications
1
76
0
9
Order By: Relevance
“…That's why financial benefits offered by a port are welcomed by shippers and liners as has been proved with numerous academic studies [e.g. 11,41,42,43,44,45,46]. However, still it is vital to note that, without high service quality, offering attractive prices will not work out.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…That's why financial benefits offered by a port are welcomed by shippers and liners as has been proved with numerous academic studies [e.g. 11,41,42,43,44,45,46]. However, still it is vital to note that, without high service quality, offering attractive prices will not work out.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Analysing port choices of all import ports in the United States, [22] concludes that distance, transport prices and individual port efficiency play a significant role in determining a port's market share. A survey of shippers [23] identified factors considered to be important port selection criteria in Nigeria. The authors identified three main criteria: efficiency, frequency of ship visits and adequate infrastructure.…”
Section: Port Competition and Selection From Literaturementioning
confidence: 99%
“…Table 2 shows various methods used by authors in measuring container port competitiveness. [20] Identify factors important to container port competitiveness in China [18] Identify important factors in transshipment port selection [27] Identify factors important to shipping lines for choice of port between Montreal and New York [23] Identify important port selection factors for shippers in Nigeria [28] Identifying main factors that influence hub port location choice in West Africa Data Envelopment Analysis (DEA) [29] Identify factors affecting efficiency of Portuguese and Greek ports [30] Identify factors affecting efficiency of Korean ports [31] Identify factors affecting efficiency of container ports [32] Determine efficiency of ports and impact on competitiveness of short sea shipping versus road transport in Europe [33] Determine impact of improving port infrastructure on cargo volumes in two Spanish ports…”
Section: Port Competition and Selection From Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Competition among various ports around the world in attracting the customers has led to privatization of ports. De Langen (2007)and Ugboma et al (2006) have identified customer focus as one of the most important factor considered by shippers in port selection. Privatization is not a new word.…”
Section: Introductionmentioning
confidence: 99%